Assessment of Lower Sakarya River Water Quality in Terms of Irrigation Water - Çiğdem Özer; Rabia Köklü (Doğal Afetler ve Çevre Dergisi)
The Lower Sakarya Sub-Basin is under the influence of the industrial activities and the wastewater from settlements, agricultural and urban run-off and the geological formations it has undergone since the birth of the Sakarya River. In spite of the effect of all these pollutant loads, it is also used for agricultural irrigation purposes. Therefore, the importance of sustainable use of this water resource for drinking and industrial use as well as for agricultural purposes is increasing. For this purpose, Lower Sakarya River quality of irrigation water for agricultural purposes has been determined. Different physical-chemical properties of water quality data belonging to 3 stations operated by State Hydraulic Works (DSI) on Sakarya River were evaluated in terms of national and international water quality standards. On the basis of these standards, irrigation water quality was interpreted by using evaluation criteria such as Electrical conductivity (EC), and Total Hardness (TH) values, Schoeller Diagram, Sodium Adsorption Rate (SAR), Sodium percentage (% Na), Magnesium Ratio (MR), Potential Salinity (PS) and Kelley index (KI).